Chloroplast lipid droplet type II NAD(P)H oxidoreductase, NDC1, is essential for vitamin E and K1 metabolism - Eugeni Piller, Lucia (My University, 2017)
Les cellules végétales possèdent dans leurs différents tissus des organelles spécialisées appartenant à la famille des plastes. Le chloroplaste est le principal membre de cette famille et il est responsable de la photosynthèse dans les plantes. La majorité des plastes contiennent des particules lipoprotéiques ("gouttelettes lipidiques") appelées plastoglobules.
Peu est connu au sujet des plastoglobules qui ont été pendant une longue période imaginés comme des gouttelettes de stockage passif. En effet, le cœur hydrophobe des plastoglobules chloroplastiques contiennent des lipides neutres comme les prénylquinones (plastoquinone, plastochromanol-8, phylloquinone, tocophérol), les caroténoïdes, les triacylglycérols, les phytyl esters et d'autres lipides inconnus.
Les plastoglobules sont aussi composés de protéines et certaines d'entre-elles participent à des réactions métaboliques qui se déroulent dans les plastoglobules.
Pendant mon doctorat, j’ai démontré que NDC1 (NADP(H) déshydrogénase C1 (At5g08740), prédite comme une NAD(P)H-dépendante réductase de quinones, est physiquement associé aux gouttelettes lipidiques des chloroplastes.
Grâce à la génétique inverse et une approche in vitro il a été démontré que NDC1 contrôle l'état redox du réservoir de plastoquinone en injectant des électrons dans le plastoquinone à l’intérieur des plastoglobules. Cet effet sur l'état redox des plastoquinones facilitent l'accumulation du plastochromanol. Nous pouvons supposer que NDC1 puisse jouer un rôle en tant que réducteur des intermédiaires quinones qui précèdent la cyclisation par VTE1.
De manière surprenante, NDC1 est requis pour la dernière étape de méthylation lors de la biosynthèse de la phylloquinone (Vitamine K1). En effet, les mutants ndc1 accumulent le précurseur non-méthylé, le 2-phythyl-1,4-naphtoquinone ce qui montre que NDC1 est une enzyme indispensable de cette voie de biosynthèse.
L’ensemble des découvertes permettent d'affirmer que les plastoglobules ne sont pas un simple lieu de stockage de lipides mais ils possèdent un rôle dans les métabolismes biosynthétique et énergétique., Plant cells in different tissues contain specialized organelles belonging to the family of plastids. The chloroplast is the most prominent family member and responsible for photosynthesis in leaves. Most plastid types contain lipoprotein particles ("lipid droplets") termed plastoglobules. Little is known about plastoglobules that were long regarded as passive storage droplets. Indeed, the hydrophobic core of chloroplast plastoglobules contains neutral lipids such as the prenylquinones, carotenoids, triacylglycerols, phytyl esters and others unknown. Plastoquinone, plastochromanol-8, phylloquinone and tocopherol are prenylquinone molecules stored partly in the plastoglobule but functioning in the chloroplast thylakoids. Plastoglobules also carry proteins and some of these have been demonstrated to participate in metabolic reactions taking place at plastoglobules.
During my PhD work I demonstrated that NDC1 (NAD(P)H dehydrogenase C1 (At5g08740)), a candidate plastoglobule protein and predicted NAD(P)H-dependent quinone reductase is physically associated with the lipid droplets. A combined reverse genetic and in vitro approach demonstrated that NDC1 controls the overall REDOX state of the total plastoquinone reservoir. NDC1 does so by reducing the plastoquinone reservoir of plastoglobules. These findings provided evidence that plastoglobules are not simply a lipid storage site but have a role in energy metabolism. Besides its effects on the plastoquinone REDOX state NDC1 also facilitates plastochromanol accumulation and, surprisingly, is required for the last methylation step in phylloquinone (Vitamin K1) biosynthesis. The ndc1 mutant accumulates the non-methylated precursor, the 2-phythyl-1,4-naphtoquinone but up to now we have been unable to determine the precise mechanism. In conclusion, I have shown that NDC1 is a unique electron input device affecting the REDOX state of the overall plastoquinone pool. But more than that NDC1 is a key player at the intersection of a variety of prenylquinone metabolic pathways. By mutant analysis, I identified that NDC1 is the second enzyme that is implicated in the tocopherol redox cycle. Presumably NDC1 plays a role as reducer of quinone intermediates foregoing the cyclization by VTE1. It has been also demonstrated that high light stress triggers far-ranging changes in prenylquinone composition studied in mutants and overexpressing lines of VTE1 and NDC1 enzymes. The discovery that NDC1 is a new component of phylloquinone biosynthesis pathway is the single most important result of my thesis.
Thèse de doctorat : Université de Neuchâtel, 2017
Keywords: Chloroplastes; plastoglobules; corps lipidiques; gradient de sucrose; prénylquinones. vitamine K1; vitamine E; plastoquinone; plastochromanol; tocopherol; lumière forte; lipidomique; cycle rédox; Chloroplasts; plastoglobules; lipid bodies; sucrose gradient; prenylquinones; vitamin K1; vitamin E; plastoquinone; plastochromanol; tocopherol; high light; lipidomics; redox cycle